NDT Testing with Visual Testing Method in the Inside Upper Frame 6015 Area with GMAW Welding Based on 1E0099 - Fajrin, Aulia; Putra, Lalu Giat Juangsa; Sutrisno, Recky (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
The Upper Frame is the most important component of the excavator because it acts as an engine mount or hose holder connected to the main control valve. So for the welding process, special attention is needed for the frame center which aims to avoid weld distortion between the right side and the left and also as a cable holder from the engine. Therefore, the welding results require special attention starting from the size of the weld and the arrangement of defects in the weld results. The welding process on the Upper Frame uses the GMAW (Gas Metal Arc Welding) process with Lincoln Merit ER70S-6 wire, where the wire size is 1.320 mm and the welding results will be tested using the NDT (Non-Destructive Testing) method, namely Visual Testing. This study aims to determine the results of visual tests in the inside Upper Frame 6015 area using the 1E0099 standard. 1E0099 is the welding procedure used at PT Caterpillar Indonesia Batam. Visual test results from GMAW (Gas Metal Arc Welding) welding are expected to be free of weld defects. If there are still weld defects found, the welding results are still within the acceptance criteria based on internal code 1E0099.